MICROBIAL DIVERSITY AND EVOLUTION IN GULF OF MEXICO HYPERSALINE ENVIRONMENTS - Nigro, Lisa (University of North Carolina at Chapel Hill Graduate School, 2015)
My thesis investigated the microbial diversity and taxonomic composition of hypersaline and non-extreme sediment environments in the Gulf of Mexico, to explore environmental controls on microbial community structure and function. Environmental conditions and resource availability are considered key drivers of microbial diversity and evolution. Extreme environments are traditionally thought to select for more specialized individuals and lower overall diversity, while non-extreme environments foster diverse communities of generalists that are capable of occupying a wider niche. However, extreme environments can also be heterogeneous and complex systems, with a wide variety of energetic resources, providing both challenges and opportunities for diversification. The sediment microbiomes of this study represented natural hydrocarbon seeps, a deep-sea hypersaline anoxic basin (Orca Basin, 26% salinity), Deepwater Horizon (DWH) oil spill-impacted sediments, and Continental Slope background sediments, all collected in November 2010. These samples were analyzed with ~5 million 16S rRNA gene amplicon sequences. Shannon diversity estimates indicated that Orca Basin hypersaline sediments, Continental Slope sediments, and DWH-contaminated surface sediments had similar species diversity, while hydrocarbon seep sediment diversity was significantly lower. UNIFRAC beta diversity analysis indicated that microbial communities inhabiting Orca Basin hypersaline sediments and hydrocarbon seep sediments had taxa unique to each of these site types, while sediments from the Continental Slope and DWH area were not statistically more similar to each other than other sediments. Taxonomic analysis showed that seep cores contained higher abundances of ANME-1 and Candidate Division JS1, while Orca Basin hypersaline sediment-associated sequences were dominated by Marine Group I Archaea, Bacteroidetes and halotolerant Deltaproteobacteria. The microbial composition of the Orca Basin brine was also investigated with 16S rRNA Sanger sequencing, ...